2015
DOI: 10.1016/j.bjp.2015.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Antigiardial activity of flavonoids from leaves of Aphelandra scabra

Abstract: Revista Brasileira de Farmacognosia xxx (2015) xxx-xxx w w w . s b f g n o s i a . o r g . b r / r e v i s t a Original Article a b s t r a c t Aphelandra scabra (Vahl) Sm., Acanthaceae, is a shrub widely used by some Mayan communities as carminative, antidote, and remedy for some infections. Bio-guided isolation of the methanol extract of leaves led us to the purification of the anti-giardial metabolites cirsimaritin and sorbifolin, along with the inactive metabolites cirsimarin, sorbifolin-6-O-␤-glucopyranos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In addition, cirsimaritin, a flavone isolated from Aphelandra scabra (Vahl) Sm., has also been described as a potent giardicidal compound (3.8 μM), and epi-catechin isolated from Rubus coriifolius Liebm. has been reported to display amoebicidal (IC 50 = 6.5 μM) and giardicidal (5.5 μM) activity (Alanís et al 2003;Hernández-Bolio et al 2015). Cirsimaritin and epi-catechin comply with the empirical structural rules for antiprotozoal activity against E. histolytica and G. lamblia.…”
Section: Resultsmentioning
confidence: 83%
“…In addition, cirsimaritin, a flavone isolated from Aphelandra scabra (Vahl) Sm., has also been described as a potent giardicidal compound (3.8 μM), and epi-catechin isolated from Rubus coriifolius Liebm. has been reported to display amoebicidal (IC 50 = 6.5 μM) and giardicidal (5.5 μM) activity (Alanís et al 2003;Hernández-Bolio et al 2015). Cirsimaritin and epi-catechin comply with the empirical structural rules for antiprotozoal activity against E. histolytica and G. lamblia.…”
Section: Resultsmentioning
confidence: 83%
“…In conclusion, lignans 1 – 8 and flavonol 9 represent two well-known classes of plant secondary metabolites [ 67 , 68 ]. The well-studied flavonoid class of natural products such as 9 display a broad range of biological activity including antiparasitic activity [ 68 , 69 ]. Likewise, lignan natural products have received strong interest and have been intensely studied due to their broad clinically relevant biological activity, including: antioxidant, antiviral, antibacterial, immunosuppressive, anti-inflammatory, and anticancer properties [ 67 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reported antiparasitic (antigiardial, antiplasmodial) and molluscicidal activities of A. coriaria could be due to the secondary metabolites identified in its extracts. For instance, flavonoids have been indicated to be effective in vitro as antigiardial agents (Barbosa, Calzada, & Campos, 2007;Hernández-Bolio, Torres-Tapia, Moo-Puc, & Peraza-Sánchez, 2015) through proapoptotic induction of cell death (Argüello-García, Calzada, García-Hernández, Chávez-Munguía, & Velázquez-Domínguez, 2020). On the other hand, antiplasmodial and antimycoplasmal activities of plant extracts are usually elicited by alkaloids, terpenoids, flavonoids, coumarins, phenolics, quinones and steroids (Bekono et al, 2020;Uzor, 2020) which have been identified A. coriaria extracts.…”
Section: Antigiardial Antiplasmodial and Molluscicidal Activitiesmentioning
confidence: 99%